Comparison of engine performance and emissions for fuels of diesel-biodiesel blends and pure biodiesel. Issue 1 (1st June 2022) - Firdaus, NK; Aunillah, A; Wardiana, E; Pranowo, D; Herman, M; Syafaruddin,
Abstract: Biodiesel is a substitute or replacement petroleum diesel fuel used to reduce pollution without modifying engines. This study aimed to investigate the engine performance and emissions characteristics of a passenger car engine (Hilux 2.4G Double cabin (4x4) M/T) fuelled by two different fuels, which is biodiesel (B100) and diesel-biodiesel fuel blend (B20). The study was conducted at the Bioenergy Laboratory of Balittri, the Thermodynamics and Propulsion Engine Research Center of BPPT, and the Research Center for Oil and Gas Technology Development (LEMIGAS), from November 2019 to February 2020. The result showed that the traction and power for diesel-biodiesel fuel blends were obtained slightly higher than biodiesel. Biodiesel has marginally higher fuel consumption than diesel-biodiesel fuel blends. According to the emission analysis, biodiesel produces lower exhaust emissions of unburned fuel emissions, carbon monoxide, and carbon dioxide content in the exhaust gas than diesel-biodiesel fuel blends.